The role of servant leadership in reducing organizational silence through knowledge sharing - Firas Tawfiq Saleh Al-Badri (Peerian Journals Publishing, 2024)
The study aims to identify the role of servant leadership behaviors represented by its dimensions (altruism, wisdom, persuasion style, emotional containment, organizational supervision) in reducing organizational silence represented by its dimensions (submissive silence, defensive self-protection, social loyalty) through knowledge sharing represented by its dimensions. (Organizational trust, organizational culture). The descriptive analytical approach was adopted, and this study was conducted at the University of Babylon. A sample of (130) individuals from the university's employees who represented senior, middle, and lower management was selected. Data was collected via a questionnaire form based on international standards. A set of hypotheses were tested. The study used a number of statistical methods and applied programs (SPSS V. 22) and (AMOS VER.20) necessary to analyze and process data. The study reached a set of conclusions and recommendations, the most important of which was a significant effect found between servant leadership behaviors and knowledge sharing to reduce Organizational silence. The most prominent recommendations were working to enhance the behaviors of servant leadership because of their positive impact on organizational work as a whole, and supporting knowledge sharing enables servant leadership to develop their cognitive ideas and become able to face the challenges facing organizational work at all levels of the university
Keywords: Servant leadership behaviors; Knowledge sharing